THE IMPLEMENTATION OF THE PROGRAM POLICY FOR PROVIDING EDUCATIONAL SCHOLARSHIPS TO OUTSTANDING STUDENTS IN PINRANG REGENCY - Siti Fatimah; Andi Aslinda; Asri Nur Aina; Nina Agustina (Universitas Negeri Makassar, 2026)
This research aims to find out about the implementation of the program policy for providing educational scholarships to outstanding students in Pinrang Regency. This research uses a case study research design with a qualitative approach. Data was obtained using observation, interviews and documentation methods. The results of the research show that the implementation of the Program Policy for Providing Educational Scholarships to Achieving Students in Pinrang Regency is quite good. This is proven based on observations and interviews conducted, on several factors proposed by George C. Edwards III (1980), namely communication, resources, disposition and organizational structure. However, in its implementation, several things were still found that needed attention and improvement. In Communication, there are three (3) indicators, there are two (2) indicators that are considered to have worked well, namely clarity and consistency. This can be seen from the overall scholarship distribution process which is considered successful, while for the transmission indicator it is said that it has not run effectively because there are still some students who sometimes don't know about the existence of this educational scholarship, even though it has been spread via social media. For resources, there is one (1) indicator that has been met, namely human resources and one (1) indicator regarding budget resources is said to be still less effective, but the time for disbursement of aid funds is slightly hampered due to several problems, so the implementation process is slightly hampered. Meanwhile, the disposition is said to have gone well in accordance with the policy to be implemented and the high willingness of the policy implementers to carry out the policy. And the bureaucratic structure is running well in implementing the educational scholarship program policy, which has been regulated by procedures and has been implemented properly based on standard operating procedures (SOP).